Design and Simulation of SPI Multi Master and Multi Slave Communication Using Arbitration Algorithm - Tharun R,; S Kishore,; Neha Hosamath,; Keerthi Kulkarni,; Vrunda Kusanur, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
In order to effectively coordinate numerous devices, ensure scalability, stability, and prevent overload on a single master, multi-master and multi-slave communication is crucial for controlling big, complex systems.Numerous techniques are currently established using I2C protocols, spi single master slave, master and multi slave communication, and others; this could cause a delay in overcoming what I'm going to build.A multi-master, multi-slave communication system is designed and simulated using verilog in Cadence tool. The architecture prioritizes synchronization and arbitration algorithm while utilizing protocols such as SPI to facilitate effective data exchange. The simulation environment provided by Cadence verifies performance indicators like power consumption, latency, and throughput. The system is scalable and reliable, as evidenced by the results, which makes it appropriate for applications involving multi-core processors, the Internet of Things and automobiles. The efficiency with which Cadence optimizes intricate communication designs is demonstrated in this paper.
Keywords: SPI; Multi-master; Multi-slave; Cadence; Efficiency